Pengaruh Tingkat Suku Bunga Dan Deposito Terhadap Peningkatan Jumlah Nasabah Aktif Pada PT Bank Tabungan Negara (Persero) Tbk Kantor Cabang Bandar Lampung Tahun 2018-2022 - Ariningrum, Hardini; Alfiana, Nanda (Universitas Malahayati, 2024)
Banks are financial institutions of business engaged in finance that provide various financial service. Fundraising activites are collecting public funds in the form of savings, savings and time deposits. The purpose oh this study was to find out how mush influence deposit rates have on increasing the number of customer at PT Bank Tabungan Negara (Persero) Tbk Bandar lampung Branch. Quantitative research method is research that emphasizes testing theory through measuring research variables with numbers and conducting data analysis with statistical procedures. The result of this study indicate that the interest rate variable partially has no significant effect on increasing the number of customers, the deposit variable partially has no significant effect of the number customers. As well the result of simultaneous testing show that the variable interest rates have no effect on increasing the number of customers at Bank BTN Bandar Lampung Branch Office 2018-2022